NILAI PENDIDIKAN PRANIKAH DALAM KITAB ‘UQUDULLUJAIN SERTA RELEVANSINYA DENGAN ISU-ISU PERNIKAHAN KONTEMPORER - Solihatunnisa, Ismi; Siti Komariah, Kokom; Budiyanti, Nurti (Qolamuna : Jurnal Studi Islam, 2025)
This study aims to analyze the pre-marital education values in the book ‘Uqudullujain by Sheikh Muhammad bin Umar Nawawi al-Bantani al-Jawi, and its relevance to contemporary marriage issues. The research method used is qualitative with a library research approach and descriptive analysis. The primary data source is the book ‘Uqudullujain, while secondary data is obtained from related books, journals, and articles. Data collection is carried out through document analysis. The findings of this study indicate that the pre-marital education in ‘Uqudullujain provides a solid foundation for building a healthy marriage, and this understanding is relevant in addressing contemporary marriage problems, such as the phenomena of "marriage is scary", child-free lifestyles, patriarchal culture, career women and the increasing cases of domestic violence (DV). The results of the study are as follows: a) the values of pre-marital education in ‘Uqudullujain related to preparation for marriage and awareness of fulfilling the rights and obligations of husband and wife, b) the relevance of these pre-marital education values in resolving contemporary marriage issues, and c) the samawa family model as a solution to build resilience in family life. Keywords : Premarital Education, Uqudullujain, Contemporary Marriage Issues